Tinjauan Kriminologis terhadap Kejahatan Pemalsuan Tanda Tangan (International Forum of Researchers and Lecturers, 2025)
The crime of forging a signature is one form of the crime of document forgery. The reasons why a person commits the crime of signature forgery and also the efforts that must be made to overcome the crime of signature forgery can be determined using criminology. Article 263 of the Criminal Code regulates forgery of documents which is punishable by a maximum prison sentence of six years. From the research conducted, to find out the causes of people committing crimes of signature forgery can be done through various approaches, namely strain theory, control theory, and differential association theory. In understanding efforts to overcome the crime of signature forgery, it can be seen from the process of law formation and the social reaction to the crime of signature forgery. The forms of social reaction to the crime of signature forgery determine what preventive measures must be taken. The social reaction of law enforcement to the crime of signature forgery can be achieved through penal or non-penal measures.